Soft-sediment deformation structures in siliciclastic sediments: an overview - van Loon, A.J. (Tom) (Bogucki Wydawnictwo Naukowe, 2009)
Deformations formed in unconsolidated sediments are known as soft-sediment deformation structures. Their nature, the time of their genesis, and the state in which the sediments occur during the formation of soft-sediment structures are responsible for controversies regarding the character of these deformations. A definition for soft-sediment deformation structures in siliciclastic sediments is therefore proposed. A wide variety of soft-sediment deformations in sediments, with emphasis on deformations in siliciclastic sediments studied by the present author, are described. Their genesis can be understood only if their sedimentary context is considered, so that attention is also paid to the various deformational processes, which are subdivided here into (1) endogenic processes resulting in endoturbations; (2) gravity-dominated processes resulting in graviturbations, which can be subdivided further into (2a) astroturbations, (2b) praecipiturbations, (2c) instabiloturbations, (2d) compagoturbations and (2e) inclinaturbations; and (3) exogenic processes resulting in exoturbations, which can be further subdivided into (3a) bioturbations – with subcategories (3a’) phytoturbations, (3a’’) zooturbations and (3a’’’) anthropoturbations – (3b) glaciturbations, (3c) thermoturbations, (3d) hydroturbations, (3e) chemoturbations, and (3f) eoloturbations. This subdivision forms the basis for a new approach towards their classification. It is found that detailed analysis of soft-sediment deformations can increase the insight into aspects that are of importance for applied earth-scientific research, and that many more underlying data of purely scientific interest can, in specific cases, be derived from them than previously assumed. A first assessment of aspects that make soft-sediment deformation structures in clastic sediments relevant for the earth sciences, is therefore provided.
Keywords: Soft-sediment deformations; Siliciclastics; Classification; Terminology